2012
DOI: 10.1007/s10792-012-9518-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes of penetrating keratoplasty versus Descemet’s stripping automated endothelial keratoplasty for penetrating keratoplasty graft failure due to corneal edema

Abstract: To evaluate the outcomes of repeat corneal transplantation, either penetrating keratoplasty (PKP) or Descemet's stripping automated endothelial keratoplasty (DSAEK), for penetrating keratoplasty grafts which failed due to corneal edema. The charts of 24 eyes with failed PKP grafts, due to corneal edema, which underwent a repeat corneal transplant (PKP in 17 eyes [Group 1] and DSAEK in seven eyes [Group 2]) between 2003 and 2007 were retrospectively reviewed. There was no statistically significant difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 22 publications
(45 reference statements)
1
21
0
2
Order By: Relevance
“…Kitzmann and associates found no statistically significant differences in postoperative BCVA between the 2 groups at 1, 2, or 3 years. 23 Similarly, we found significant improvement in postoperative BCVA in both groups and at 1 year, but no significant differences in BCVA at the 1 year follow-up between the repeat PK group and EK under PK group (P ¼ .185).…”
Section: In This Study We Directly Compared Subjects Whosupporting
confidence: 60%
See 4 more Smart Citations
“…Kitzmann and associates found no statistically significant differences in postoperative BCVA between the 2 groups at 1, 2, or 3 years. 23 Similarly, we found significant improvement in postoperative BCVA in both groups and at 1 year, but no significant differences in BCVA at the 1 year follow-up between the repeat PK group and EK under PK group (P ¼ .185).…”
Section: In This Study We Directly Compared Subjects Whosupporting
confidence: 60%
“…37 In this nested study from our prospective cohort of corneal grafts, we found significantly prolonged graft survival in eyes that underwent EK under a failed PK, compared to the repeat PK group at up to 5 years followup (cumulative survival probability 86.4% vs 51.3%, respectively, log-rank P value ¼ .013). This suggests a significant long-term graft survival advantage of performing EK under a failed PK in patients who suffer initial corneal 14,23 and 21%-70% for repeat PK. [10][11][12][13][14][15][16][17][18] Of note, graft rejection episodes were more common in the repeat PK group compared to the EK under PK group, albeit nonsignificant, likely owing to the small sample size (13.6% vs 3.1%, P ¼ .174)-despite having no significant differences in immunosuppression regime.…”
Section: In This Study We Directly Compared Subjects Whomentioning
confidence: 99%
See 3 more Smart Citations